Retrospective evaluation of sarcoidosis cases: 10 years of experience from Turkey (Annals of Medical Research, 2021)
Aim: Clinical features in sarcoidosis are very variable and can present with numerous phenotypes depending on organ involvements, clinical onset (acute, subacute, and chronic) and response to therapy. In this study, we aimed to evaluate the clinical findings, diagnostic methods and treatments of patients with sarcoidosis by 10-years data in our hospital in Turkey.Materials and Methods: The study was carried out between January 2018 and January 2019. The patients were screened retrospectively from the hospital information system. Clinical details were collected using a structured data collection form.Results: 172 patients were included in our study. 122 (70.9%) were female and 50 (29.1%) were male. The mean age at diagnosis was50.18 ± 13.73 years in all patients, while female patients’ mean age was 52.86 ± 13.06, male patients’ was 43.66 ± 13.24 (p
Keywords: Arthralgia; EBUS; Sarcoidosis; Serum ACE